Management of Severe Dento-Alveolar Traumatic Injuries in a 9-Year old Boy: A Case Report - Mousavi, Elnaz; Khoshdel, Masoomeh; Sharifiyan, Hamidreza (UI Scholars Hub, 2021)
Dentoalveolar traumas can lead to various injuries that may result in tooth loss. A suitable treatment plan and appropriate interventions should be performed to maintain the dental function and aesthetics, especially for the anterior teeth. Objective: To report the interventions performed on dentoalveolar trauma on a 9-years old male patient who presented with gingival immersion of the right maxillary central incisor and missing a tooth due to a falling accident. Case Report: The patient had multiple traumatic injuries. The medical and dental history was taken, and the clinical and radiologic examinations were performed. The patient underwent surgical intervention and splinting to take the intruded tooth back into its normal place. Moreover, the teeth with lateral luxation underwent apexification and composite filling. Also, endodontic treatment was performed on the coronal segment of the tooth with root fractures. The patient underwent clinical and radiographic follow-up for 24 months to assure the treatment efficiency and prevent further complications. Conclusion: It was shown that the interventions performed could preserve the function and aesthetics of the patient’s teeth, which can directly impact his quality of life and emotional state in adolescence.